Environmental Genotoxicity Assessment Using Micronucleus (and Nuclear Abnormalities) Test on Intertidal Mussel Perumytilus purpuratus: A Tool for Biomonitoring the Chilean Coast - Musrri, C. A.; Palma-Rojas, C.; von Brand, E.; Abessa, D. M.S. [UNESP] (Springer Nature, 2021)
The release of pollutants is increasing along the coast of Chile, and the use of biomarkers in biomonitoring programs is essential to assess the early biological effects of marine contamination. The Micronucleus (MN) test was carried out using hemocytes of the mussel Perumytilus purpuratus from two sites in northern-central Chile (La Pampilla and Totoralillo). Nuclear abnormalities were assessed, and high frequencies of micronucleus (10.7–14.4‰) and other abnormalities were found (51.9–76.6‰). These values tended to be higher in La Pampilla, possibly due to the large presence of pollution sources in that site. However, considerably high values were observed in both sites. P. purpuratus is a suitable bioindicator and further monitoring along the Chilean coast using this species should be developed using the MN test and/or other biomarkers to comprehend the effects of human activities on the coastal environment of Chile.
Keywords: Biomonitoring; Chile; Genotoxicity; Micronucleus; MN test; Perumytilus purpuratus